Decomposition of Picolyl Radicals at High Temperature: A Mass Selective Threshold Photoelectron Spectroscopy Study. Issue 72 (5th December 2019) - Reusch, Engelbert; Holzmeier, Fabian; Gerlach, Marius; Fischer, Ingo; Hemberger, Patrick
Abstract: The reaction products of the picolyl radicals at high temperature were characterized by mass‐selective threshold photoelectron spectroscopy in the gas phase. Aminomethylpyridines were pyrolyzed to initially produce picolyl radicals ( m / z =92). At higher temperatures further thermal reaction products are generated in the pyrolysis reactor. All compounds were identified by mass‐selected threshold photoelectron spectroscopy and several hitherto unexplored reactive molecules were characterized. The mechanism for several dissociation pathways was outlined in computations. The spectrum of m / z =91, resulting from hydrogen loss of picolyl, shows four isomers, two ethynyl pyrroles with adiabatic ionization energies (IEad ) of 7.99 eV (2‐ethynyl‐1 H ‐pyrrole) and 8.12 eV (3‐ethynyl‐1 H ‐pyrrole), and two cyclopentadiene carbonitriles with IE′s of 9.14 eV (cyclopenta‐1, 3‐diene‐1‐carbonitrile) and 9.25 eV (cyclopenta‐1, 4‐diene‐1‐carbonitrile). A second consecutive hydrogen loss forms the cyanocyclopentadienyl radical with IE′s of 9.07 eV ( T 0 ) and 9.21 eV (S1 ). This compound dissociates further to acetylene and the cyanopropynyl radical (IE=9.35 eV). Furthermore, the cyclopentadienyl radical, penta‐1, 3‐diyne, cyclopentadiene and propargyl were identified in the spectra. Computations indicate that dissociation of picolyl proceeds initially via a resonance‐stabilized seven‐membered ring. Abstract : The picolyl radical is a crucial intermediate in reactive environments, for example, the combustion of biofuels. Its unimolecular dissociation products at high temperature were characterized by mass‐selective threshold photoelectron spectroscopy and several hitherto unexplored reactive molecules were characterized.